Observation of chiral Landau levels in a synthetic acoustic Weyl semimetal - Kaichong Li; Xuan Zhang; Zhiwang Zhang; Ying Cheng; Xiaojun Liu (Communications Physics)
Abstract Band degeneracies, such as Dirac/Weyl points, play crucial roles in topological materials and condensed matter physics. Magnetic fields in Weyl systems induce the zeroth chiral Landau level, of which the concept has been extended to classical wave systems. While current research predominantly focuses on three-dimensional (3D) systems, exploring chiral Landau levels in two-dimensional (2D) systems, particularly through the introduction of an out-of-plane magnetic field, remains a vibrant area of study. Here, we report the observation of chiral Landau levels in 2D sonic crystals using the synthetic dimension methodology. By applying an out-of-plane pseudo-magnetic field generated through gradient deformation, we measure the dispersions of zeroth chiral Landau levels originating from synthetic Weyl points. Experiments also reveal sub-lattice polarizations of the chiral Landau levels. Our work demonstrates pseudo-magnetic-field-induced Weyl physics in a 2D system without breaking time-reversal symmetry, enabling exploration of topological phenomena and related acoustic wave control strategies.